July 2024, Osman Hadi and Khaleda Zia - Hasan, Md. Mahmudul (Media New Age Limited, 2026)
In post-July 2024 Bangladesh, people of the country have two choices. They can remember the selflessness and sacrifice of our July 2024 warriors — who lost their lives and limbs for freedom and justice — and work hard to realise their dreams. Or, they can be ungrateful to them and forgetful of who (within the country and beyond) were responsible for Khaleda Zia’s woes. Even though historical precedence is slanted towards the latter, the unity that the people of Bangladesh demonstrated during the funeral of Osman Hadi and Khaleda Zia gives us hope that they will never open the door for fascism and tyranny to return to Bangladesh again.